Estimation of serum ferritin and TSH levels in thalassemia patients undergoing iron chelation therapy (Bangladesh Journal of Medical Science, 2021)
Objectives & introduction: Thalassemia, heterogenous group of disorders of haemoglobin,characterised by reduced or absent production of one or more of globin chains.Regular redcell transfusion with chelation therapy for iron overload are cornerstones of therapy for ßthalassemia major. Serum ferritin assay is widely available, relatively inexpensive methodfor assessing body iron burden and monitoring response to chelation process which in turnalso improves TSH levels in thalassemic subjects .The objective of this study was to assessprechelation and postchelation levels of serum ferritin and TSH and correlating post chelationlevels of serum ferritin and TSH in thalassemic patients >6yrs undergoing chelation therapy.Materials & methods: Serum TSH measured by Enzyme linked fluorescent assay and serumferritin measured by enzyme linked immunosorbent assay.Results: Amongst 500 participants,47% were males & 53% females. Mean age was 9.04 yrs ;prechelation ferritin and TSH levelswere 2995.78ng/ml with SD of 802.53 and 5.07 μU/ml with SD of 2.52. The postchelationferritin and TSH levels were 2168.80 ng/ml with SD of 1335.89 and 4.51μU/ml with SD of4.76. Paired t test with respect to pre and postchelation ferritin and TSH levels showed 2 tailed pas 0.000 and t>3, both of which considered significant. While correlating post chelation ferritinwith TSH levels; they showed a linear correlation ( Pearson coefficient of .836).Conclusion:Serum ferritin and TSH estimation in prechelation and postchelation periods give an estimateof iron overload with effect of chelation on it. Both levels decrease post chelation presenting alinear correlation between the two.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.130-135